Investment banking: Valuation, LBOs, M & A, and IPOs - Rosenbaum, Joshua; Pearl, Joshua (New jersey John Wiley & Sons, Inc., 2021)
Investment Banking provides a highly practical and relevant guide to the valuation analysis at the core of investment banking, private equity, and corporate finance. Mastery of these essential skills is fundamental for any role in transaction-related finance. This book will become a fixture on every finance professional$1 (Bs bookshelf.s